Morphological, Physiological, Biochemical and Molecular Facet of Drought Stress in Horticultural Crops - Kumar, R.; Berwal, M. K.; Saroj, P. L. (International Journal of Bio-resource and Stress Management, 2019)
Water stress disrupts horticultural crop growth, development and finally results in low productivity particularly in arid and semi arid parts of the world. Plants require certain physical, chemical and biological factors for their growth and development. Any deviation from these factors may cause aberrant metabolic changes and plant experience a tension known as stress. Water stresses trigger a wide variety of plant responses, ranging from altered gene expression and cellular metabolism to changes in plant growth, leaf morphology and movement and root development and finally productivity. Drought stress modifies photosynthetic rate, relative water content, leaf water potential, and stomatal conductance. Finally, it destabilizes membrane structure and permeability, protein structure and function, leading to cell death. Drought tolerant plants possess various mechanisms like reduction in water loss by reducing stomatal conductance or morphological modification, improving water uptake by developing efficient root systems and accumulation of osmolytes. Management practices employed for drought stress management in horticultural crops include use of drought tolerant crop varieties, use of tolerant root stocks, canopy management, wind breaks, regulated deficit irrigation and partial root zone drying, uses of anti-transpirants etc. The varieties selected should have deep root system (bael, ber), leaf shedding (ber, lasoda, pomegranate), thorns on stem (ker, karonda, ber), stomata at lower side (custard apple), wax coating (ber), thin foliage and leaf orientation (aonla), hair on leaf and sunken stomata (fig, phalsa, ber and lasoda). This paper elaborates physiological, biochemical and molecular mechanism of drought tolerance along with drought stress management in horticultural crops.